'I didn't do anything, I just watched': perspectives of Brazilian students with physical disabilities toward physical education. Issue 10 (23rd August 2020) - Tanure Alves, Maria Luíza; Grenier, Michelle; Haegele, Justin A.; Duarte, Edison
ABSTRACT: Teachers in physical education (PE) classes continue to face problems promoting effective participation of students with disabilities. To better comprehend these issues, we need to advance discussions on PE programming and curricula, as well as the values about ability and performance that are communicated through these mediums. Difficulties with inclusion in this specific educational context are associated with more than simply a lack of adaptations in activities, but with values embedded in practices associated with disability. The purpose of this study was to analyse the inclusion of students with physical disabilities in PE classes through a cultural analysis of curriculum, disability and PE. Data were collected through semi-structured face-to-face interviews and reflective field notes. Seven students with physical disabilities enrolled in different schools in urban regions of a Brazilian city participated in this study. The interviews were examined through content analysis technique by two researchers, with categorisation into thematic categories. Findings include enacted values of sports practices where performance and ability are prioritised. A lack of participation was associated with curricular choices and values presented by PE teachers. The effectiveness of the inclusion process in PE class is discussed.